Soil Organic Carbon Dynamics in Two Rice Cultivation Systems Compared to an Agroforestry Cultivation System (2021)
After changes in tillage on croplands, it is necessary to assess the effects on soil organic carbon (SOC) dynamics in order to identify if soil is a sink or emitter of carbon to the atmosphere. This study was conducted in two plots of rice cultivation, where tillage and water management changes occurred. A third plot of native forest with Cacao trees was used as reference soil (agroforestry). For SOC balance estimation, measurement of organic carbon (OC) inputs was determined from necromass, roots, microbial biomass, and urea applications. CO2 and CH4 emissions were also measured. Results showed that the change in the use of irrigation and tillage in rice cultivation did not cause significant differences in OC inputs to soil or in outputs due to carbon emissions. Further-more, it was found that both irrigation and tillage management systems in rice cultivation com-pared with agroforestry were management systems with a negative difference between OC inputs and outputs due to CO2 emissions associated with intense stimulation of crop root respiration and microbial activity. The comparison of SOC dynamics between the agroforestry system and rice cultivation systems showed that an agroforestry system is a carbon sink with a positive OC dynamic.